Conscious Knowledge, Unconscious Practice: Rethinking Teacher Awareness in Phonological Instruction - Wildan Sani Rasyid (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2025)
This study seeks to reconceptualize teacher awareness by critically examining the discrepancy between teachers’ stated beliefs about the International Phonetic Alphabet and their actual classroom practices in English as a Foreign Language context. The study is grounded in the problem that teacher awareness is often narrowly defined as declarative knowledge, without sufficient attention to how such knowledge is enacted pedagogically. Employing a qualitative case study design, the research involved three Indonesian English as a Foreign Language teachers at UIN Ar-Raniry and utilized questionnaires, semi-structured interviews, and direct classroom observations to triangulate data on declarative knowledge and procedural practice. The findings reveal a clear paradox: although all participants demonstrated strong conscious endorsement of the importance of the International Phonetic Alphabet for phonological instruction, none explicitly applied it in classroom practice, instead relying on intuitive and implicit instructional strategies. This disjunction indicates that theoretical knowledge alone does not ensure pedagogical enactment. The study argues that teacher awareness should be understood as a multi-layered construct integrating both conscious knowledge and proceduralized practice. Consequently, teacher education programs must move beyond theory transmission toward the systematic development of practical, embodied instructional skills.